144 Selective inhibition of plasma membrane calcium atpase 4 improves vegf-mediated angiogenesis. (5th June 2017) - Kurusamy, Sathishkumar; López-Maderuelo, Dolores; Little, Robert; Cadagan, David; Savage, Aaron M; Ihugba, Jude C; Baggott, Rhiannon R; Rowther, Farjana B; Martinez-Martinez, Sara; Arco, Pablo Gomez del; Murcott, Clare; Wang, Weiguang; et al.
Abstract : Ischaemic cardiovascular disease is the leading cause of death worldwide. Therapeutic angiogenesis aims to stimulate the growth of new blood vessels from pre-existing ones to reperfuse ischaemic tissues. Our laboratory is characterising the molecular mechanisms that regulate activation of the calcineurin/NFAT pathway during VEGF-induced angiogenesis. We recently showed that the Plasma Membrane Calcium ATPase 4 (PMCA4) negatively regulates angiogenesis by establishing a molecular interaction with calcineurin. The identification of aurintricarboxylic acid (ATA) as an inhibitor of PMCA4 prompted us to hypothesise that ATA will enhance VEGF-induced angiogenesis. Consistent with this hypothesis, we demonstrate in this work that inhibition of PMCA4 by treatment with ATA significantly increases the activity of calcineurin/NFAT signalling, and the subsequent expression of the NFAT-dependent, pro-angiogenic protein RCAN1.4 in VEGF-stimulated endothelial cells. Targeting PMCA4 with ATA significantly reduces the level of membrane-associated calcineurin, and the amount of calcineurin co-precipitated with PMCA4 in immunoprecipitation assays, indicating that ATA promotes disruption of the PMCA4/calcineurin interaction. ATA robustly enhances endothelial cell motility, and in vitro and in vivo blood vessel formation, with no harmful effects to the cells. Interestingly, incubation of HUVECs with low concentration of ATA had no effect on the viability of the cells or the development of zebra fish embryos. However, higher ATA concentrations were associated with cellular and embryo toxicity. Our study provides evidence for the therapeutic potential of targeting endothelial PMCA4 to improve VEGF-based pro-angiogenic interventions, and highlights possible clinical applications for PMCA4 inhibitors in the treatment of ischaemic cardiovascular disease.